Peningkatan Deteksi Dini Risiko Tinggi Persalinan melalui Edukasi dan Skrining Terpadu pada Wanita Usia Subur - Eko Sri Wulaningtyas; Dhewi Nurahmawati; Ardina Rezky Noeraini; Entin Srihadi Yanti; Pingkan Listia Putri; Niken Ayu Damayanti (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
High-risk pregnancy and childbirth remain major contributors to maternal and neonatal mortality in Indonesia. Limited knowledge among women of reproductive age regarding pregnancy risk factors and delayed early detection are common community problems. This community service program aimed to improve knowledge and conduct early detection of high-risk childbirth through integrated education and screening. The activity was conducted in the working area of Balowerti Public Health Center, Kediri City, involving 20 women of reproductive age. Methods included reproductive health education, early risk screening, counseling, and evaluation using pre-test and post-test. Results showed an increase in average knowledge scores from 56 to 84 (50% improvement). Screening results indicated that 60% of participants were not at risk, 30% had moderate risk, and 10% were categorized as high risk and received further counseling and referral. This program effectively enhanced participants’ knowledge and supported preventive efforts to reduce pregnancy and childbirth complications